2005
DOI: 10.1111/j.0391-5026.2005.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Trade Credit Substitute Bank Credit? Evidence from Firm-level Data

Abstract: The paper examines micro data on Italian manufacturing firms' inventory behaviour to test the Meltzer (1960) hypothesis according to which firms substitute bank credit with trade credit (TC) during money tightening. We find that inventory investment of Italian manufacturing firms is constrained by their availability of TC and that this effect more than doubles during monetary restrictions. As for the magnitude of the substitution effect, however, we find that it is not sizeable. This is in line with the micro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 38 publications
6
59
0
4
Order By: Relevance
“…The dependent variable, following Blasio (2005) is the ratio of the difference between debtors and creditors to total assets -trade credit (TC). To examine how the company i resorts the credit from suppliers when facing different values of banking financing in studied periods, we use the variable bank credit (BC) which has been proxied with the ratio of bank debt to total assets as an independent variable.…”
Section: Methodsmentioning
confidence: 99%
“…The dependent variable, following Blasio (2005) is the ratio of the difference between debtors and creditors to total assets -trade credit (TC). To examine how the company i resorts the credit from suppliers when facing different values of banking financing in studied periods, we use the variable bank credit (BC) which has been proxied with the ratio of bank debt to total assets as an independent variable.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, even in developed financial markets, when monetary authorities are conducting a restrictive policy, the supply of external finance may decrease significantly, such that a sufficient allocation of funds to all demanding borrowers may no longer be possible, creating the need for alternative channels to finance growth. Several empirical studies have shown that firms substitute bank loans for trade credit in an effort to limit the impact of the traditional bank lending channel (Nilsen, 2002;De Blasio, 2005;Choi and Kim, 2005;Guariglia and Mateut, 2006) or, as shown in Figure 2, to limit the impact of a financial crisis (Love et al, 2007). .…”
Section: Implications Of Country Heterogeneitymentioning
confidence: 99%
“…In Italy, the weight of trade credit has been traditionally important (De Blasio, 2005;Marotta, 2005;De Socio, 2010;Agostino & Trivieri, 2013). Data used in this paper and described afterwards, indicate that trade credit accounts on average for 24.9% of firms' total liabilities.…”
Section: Introductionmentioning
confidence: 84%